Schemes of Scaffolding in Online Education - Ni Komang Arie Suwastini; Ni Putu Dewi Ersani; Ni Nyoman Padmadewi; Luh Putu Artini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Scaffolding in learning has been argued to facilitate the students’ progress. As the educational paradigm inevitably shifts into online modes, strategies for scaffolding provision need to be adjusted. This study aimed to understand the nature of the online learning environment and explore the aspects, types, and methods of scaffolding provision in online learning contexts by adopting George's (2008) research method into a qualitative design. The data were collected from experts' opinions and previous studies, as published in reputable international journals, using Education Resources Information Center (https://eric.ed.gov/), Google Scholar (https://scholar.google.com), and Research Gate (https://www.researchgate.net) as the databases. The research result is presented in an informal method. The review reveals that critical aspects of scaffolding are contingency, fading, and transfer of responsibility, which are applicable in synchronous and asynchronous learning with the support provided by peers, teachers, or technology through static or dynamic interaction. Based on its purpose, the four types of scaffolding are procedural, conceptual, metacognitive, and strategic, which can be performed strategically in online contexts through orientation to the course structure, access to resource and tools, critical thinking development, guidance to problem-solving, provisions of hints, sufficient examples, probing questions, and providing constructive feedback. These findings imply the importance of implementing scaffolding strategies in online learning contexts, although further studies need to be conducted to provide more comprehensive scaffolding models.